(untitled) (Colombia Medica, 2008)
Pyoderma gangrenosum is an entity of unknown etiology, with diverse expressions, mainly on skin. Their differential diagnosis are difficult and broad, and do not have a clear therapy of choice. The response to therapy is variable, with failure in many opportunities. A case of a 40 year old woman with extensive and severe pyoderma gangrenosum having 5 years of evolution is discussed. Her therapy response to multiple medications had been poor but she showed a dramatic answer to rifampicine.